Prophylactic and therapeutic vaccines against sporotrichosis. Feasibility and prospects - Téllez-Martínez, Damiana [UNESP]; Batista-Duharte, Alexander [UNESP]; Portuondo, Deivys Leandro [UNESP]; Carlos, Iracilda Zeppone [UNESP] (Elsevier, 2019)
Sporotrichosis is an emergent subcutaneous mycosis of humans and some animals caused by dimorphic fungi of the genus Sporothrix. The disease occurs worldwide but is endemic or hyperendemic in tropical and subtropical areas. The epidemiology of the disease is changing dramatically, and it is now considered an important zoonosis with high morbidity rates, principally in Brazil, and an opportunistic infection in immunocompromised patients. Due to the limited options currently available to treat invasive fungal infections, including sporotrichosis, and the emergence of drug resistance and toxicity, the development of anti-Sporothrix vaccines has become an area of great interest. This work provides a brief analysis of the feasibility of the development of prophylactic and therapeutic vaccines against sporotrichosis, the main advances achieved to date, future challenges and prospects.
Keywords: Adjuvants; Antigens; Sporothrix schenckii; Sporotrichosis; Vaccine development